Effect of Weather on Cocoa and Improvement of Bean size Through Seasonal Crop orientation - Prameela K P (Department of Agronomy, College of Horticulture, 1997)
With an objective of understanding the probable reasons for seasonal fluctuations in flowering and fruiting and also to orient the cocoa crop to a season favourable for bean size, a four year investigation was carried out at the College of Horticulture, Vellanikkara during 1993-96. The influence of weather variables on flowering was studied by correlating weekly flower production with weather parameters of previous one to twelve weeks. This was done using plants with and without fruit load. Flower production was also correlated with increase in fruit load of previous one to twelve weeks. The possible effects of soil moisture deficit and surplus on flowering was also studied. The influence of weather on fruiting was studied by correlating monthly pod yield with weather variables of previous one to seven months. The influence of fruit load on fruiting was also studied by correlating monthly pod yield with increase in fruit load of previous one to seven months. For crop orientation study two sets of plants were used, one as control and the other as treatment. The plants used as control were retained as such without disturbing pods. In the other set, defloration was done excepting during the period from April to July. The results revealed that maximum temperature and bright sunshine hours were positively correlated with flower production while rainfall, relative humidity and number of rainy days were negatively' correlated. However, summer rains had positive effect. Fruit load had negative influence on flowering. For pod production the seasonal difference was much pronounced. During monsoon season a comparatively dry condition with high temperature and low relative humidity caused high pod production after five to six months, while in a non-monsoon period production was favoured by high humidity and high rainfall. Pod load affected flower and fruit production adversely. Models were developed to predict flower and fruit production from weather variables and pod load. The crop orientation study showed that the crop could be oriented to the favourable season of October-November without affecting the total annual yield. However, during years of heavy incessant rains the practice may fail.